MANAJEMEN PEMBELAJARAN PAI DI KELAS VIII DALAM PENINGKATAN KARAKTER RELIGIUS SISWA DI SMPN 1 MOJOWARNO JOMBANG - M. Sholahuddin Akbar; Nur ‘Azah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The growth of religious character in students is one of the important roles in Islamic Religious Education (PAI). This religious character is manifested through a series of traits, morals, values and attitudes that are reflected in the individual's beliefs, religious practices and moral behavior. This goal can be achieved through effective PAI learning management. Proper PAI learning management will help teachers in designing, implementing and evaluating PAI learning in a systematic and directed manner. This aims to optimize the learning process and develop students' religious character to the maximum. Research aims: 1). To describe PAI learning planning in class VII in improving students' religious character at SMPN 1 Mojowarno Jombang. 2). To describe the implementation of PAI learning management in class VIII in improving the religious character of students at SMPN 1 Mojowarno Jombang. 3). To describe the evaluation of PAI learning in class VIII in improving the religious character of students at SMPN 1 Mojowarno Jombang. The model used in this research is a case study with a descriptive qualitative approach. Research informants consisted of school principals, curriculum representatives, student affairs representatives, PAI teachers, and students. This research collects data using interview, observation and documentation instruments as well as analyzing data using data reduction, data display and verification. Meanwhile, in testing data validity, the criteria for credibility, transferability, dependability and confirmability are the four basic criteria. Based on the research results, it can be concluded 1). Planning PAI learning in the classroom to improve students' religious character, namely determining specific goals, determining the teaching and learning process, determining learning references, and determining learning media. 2). The implementation of Pai's teaching and learning process in class VIII in improving students' religious character consists of 3 stages, namely the preliminary, core and closing processes. 3). Evaluation of PAI learning in class VIII in improving students' religious character in the form of determining evaluation of learning outcomes, data collection, data management and analysis, sustainability of actions and evaluation results